Lonely, anxious, and uncertain: Critical risk factors for suicidal desire during the COVID-19 pandemic. (October 2021) - Allan, Nicholas P.; Volarov, Marija; Koscinski, Brandon; Pizzonia, Kendra L.; Potter, Kaley; Accorso, Catherine; Saulnier, Kevin G.; Ashrafioun, Lisham; Stecker, Tracy; Suhr, Julie; Allan, Darcey M.
Highlights: We examined the relations between suicidal desire and risk factors for suicide. Loneliness was uniquely associated with increased suicidal ideation. Anxiety sensitivity was uniquely associated with increased suicidal ideation. Intolerance of uncertainty correlated with increased suicidal ideation. Abstract: Public health measures enacted early in response to the COVID-19 pandemic resulted in unprecedented physical isolation. Social isolation, or the objective experience of being alone, and loneliness, the subjective feeling of being lonely, are both implicated in suicidal ideation. Anxiety sensitivity (i.e., fear of somatic anxiety) and intolerance of uncertainty (distress due to uncertainty), may also be heightened in response to the pandemic increasing risk for suicidal ideation in response to social isolation and loneliness. The direct and interactive relations loneliness, anxiety sensitivity, and intolerance of uncertainty shared with suicidal ideation were examined using structural equation modeling across two samples. Sample 1 comprised 635 people ( M age = 38.52, SD = 10.00; 49.0% female) recruited using Mechanical Turk in May 2020. Sample 2 comprised 435 people ( M age = 34.92, SD = 14.98; 76.2% female) recruited from faculty, staff, and students at a midwestern university in June 2020. Loneliness and anxiety sensitivity were positively, uniquely associated with suicidal ideation across samples. Results of this study were cross-sectional and included only self-report measures. These findings highlight loneliness and anxiety sensitivity as important correlates of suicidal ideation. Modular treatments should be employed to target these mechanisms to reduce COVID-19-related suicidal ideation.